The reality of kindergarten buildings in Hama city from the perspective of kindergarten directors ((A field study on kindergartens in Hama city)) (Journal of Hama University, 2026)
The current research aimed to identify the reality of kindergarten buildings in the city of Hama from the perspective of kindergarten directors. The research adopted a descriptive and analytical approach. The research tool was a monitoring list, which was constructed based on the conditions for licensing kindergartens in the Syrian Arab Republic. The research sample consisted of (56) kindergarten directors.The research results indicated the following:   -The reality of kindergarten buildings in Hama city, from the directors' perspective, was average (60%), followed by (22.50%) who considered it low, and (17.50%) who considered it high.-There were statistically significant differences between the average scores of the research sample members on the checklist for the reality of kindergarten buildings in Hama city according to the variable of kindergarten type, with the differences favoring private kindergartens.-There are statistically significant differences between the average scores of the research sample members on the two sub-axes (building components, health safety) and the total score of the kindergarten building monitoring list according to the licensing year variable, in favor of kindergartens whose licensing year is (5-10) years.
Keywords: Buildings - Kindergartens - kindergarten buildings